PENGARUH KONSUMEN DALAM PEMBELIAN SEPATU BERMEREK DI KOTA BATAM - Golan Hasan (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2021)
The purpose of this study is to analyze the influence of consumers in purchasing branded shoes in Batam City and also the influence of Brand Awareness, Perceived Quality, Perceived Value, Brand Personality, Organizational Associations and also the last is Brand Uniqueness to Brand Loyalty. Processing the data using the PLS program facility.The data obtained is by distributing questionnaires as many as 283 to the respondents. This research uses a google form link that is distributed to millennial communities in Batam City.The results of this study indicate that there is a significant positive effect of Brand Awareness, Brand Personality, Organizational Associations and Brand Uniqueness on Brand Loyalty, while Perceived Quality and Perceived Value show no significant influence on Brand Loyalty.This study is to determine how loyal consumers are in purchasing branded shoes through several factors such as Brand Awareness, Perceived Quality, Perceived Value, Brand Personality, Organizational Associations and also the last one is Brand Uniqueness. Keywords: Brand Awareness, Perceived Quality, Perceived Value, Brand Personality, Organizational Associations, Brand Uniqueness, Brand Loyalty.